P.55: A Study of Optimal Viewing Distance in an AS3D Display. Issue 1 (1st July 2013) - Hsu, Wan‐Hsuan; Huang, Kuo‐Chung; Chou, Yi‐Heng; Lin, Lang‐chin; Lin, Hoang Yan; Chen, Fu‐Hao; Liao, Ching‐Chiu; Chen, Yi‐Han; Lee, Kuen
Abstract: Optimal Viewing Distance (OVD) is a basic and important auto‐stereoscopic 3D (AS3D) display characteristic. A number of studies, especially in the 3D display design and metrology fields, have mentioned this item for a long time. Unfortunately, there have been few theoretical and empirical studies on OVD. In this paper, we study OVD based on designer's formula, and geometrical and ray tracing approaches are applied to the simulation and measured data. We find that the OVD no more exist in practical cases, and we suggest the thought OVD should be modified by designated eye position (DEP).